Detection, characterization and pathogenicity of Coleus blumei viroid in Coleus blumei Benth. in peninsular Malaysia - Che Roslan, Nurul Najwa (2019)
Plectranthus scutellarioides or synonym known as Coleus blumei is a popular ornamental plant in Malaysia grown for beautification as garden plants and mostly used for landscape due to their brightly colour foliage. However, this plant is susceptible to infection of six variants of Coleus blumei viroid (CbVd-1 to CbVd-6) of genus Coleviroid from family Pospiviroidae. CbVd is distributed worldwide, but yet to be reported in Malaysia. Inadequate information on viroid disease in ornamental plant species, specifically C. blumei in Malaysia is of concern for the landscape industry. In view of this, the objectives of this study were (a) to detect and characterize of CbVd from C. blumei benth. in Peninsular Malaysia using RT-PCR, cloning and sequencing, (b) to study the pathogenicity of CbVd-1 and CbVd-5 on C. blumei cultivar ‘Dipt in wine’. Altogether, 49 samples of C. blumei showing viroid-like symptoms such as stunted growth, faded leaf colour and reduction in leaf size and nonsymptomatic consists mixed cultivars were sampled from Perlis, Kedah, Perak, Selangor, Melaka, Kelantan and Johor. RT-PCR was used to detect CbVd using three sets of CbVd primers (universal CbVd primer, specific CbVd1K and specific CbVd- 5 primer). Results of molecular detection by RT-PCR showed that 47 of 49 samples were positive for CbVd (CbVd universal primer), 45 samples were positive with CbVd-1 (CbVd1K primer) and 41 samples were positive with CbVd-5 (CbVd-5 primer). Meanwhile, mixed infection of both CbVd-1 and CbVd-5 variants were detected in 40 out of 49 collected samples. All nucleotides of CbVd-1 and CbVd-5 positive samples were 249-250 nt and 274 nt in length. Sequence analysis of both CbVd-1 (MF176948-MF176951) and CbVd-5 clones (MF176952-MF176955) revealed 99% to 100% sequence similarity to CbVd-1 clone 1, complete genome (GenBank Accession No. DQ178399.1) and Korea (GenBank Accession No. EU410620.1) and CbVd-5 clone 1, complete genome (GenBank Accession No. FJ151370.1) from China. Results from phylogenetic analysis of the Malaysian CbVd- 1 with isolates from Korea, India, China, Brazil and Germany showed that the Malaysian isolates formed same clade with Korea (EU410620), India (AB740017 and AB740018), China (DQ178397- DQ178399) and Brazil (X69293) meanwhile CbVd 5 isolates with isolates from China (FJ151370-FJ151372 and NC012127) and Japan (LC068970). Pathogenicity study showed that C. blumei cultivar ‘Dipt in wine’ seedlings inoculated with leaf sap and plasmid containing a CbVd-1 (CbVd-1_J1MY) and CbVd-5 insert (CbVd-5_R3MY) expressed only leaf colour fading symptom meanwhile inoculated seedlings with leaf sap and plasmid containing combination of both CbVd variants (CbVd-1_J1MY and CbVd-5_R3MY) showed leaf colour fading and stunting over 12 weeks observation period. CbVd-1, CbVd-5 and combination of both variant were detected in C. blumei cultivar ‘Dipt in wine’ seedlings between 3 to 9 weeks post-inoculation by RT-PCR. Sequencing of the amplicons confirmed the presence of CbVd-1, CbVd-5 and mixed infection with more than 95% sequence similarity with CbVd-1 (CbVd-1_J1MY) and CbVd-5 variants (CbVd-5_R3MY) that were used for the inoculation. In summary, CbVd-1 and CbVd-5 were present in C. blumei in Peninsular Malaysia and they were able to replicate in C. blumei cultivar ‘Dipt in wine’. This is the first report of CbVd-1 and CbVd-5 in Malaysia.